ENVIRONMENT, PROBLEMS AND COMPETENCY FACTORS RELATED TO THE INNOVATION COMPETENCY MODEL OF DANCE TEACHERS FOR LEARNING MANAGEMENT - Prasert, Tarada; Chinpong, Sureerat; Trakoonvorakun, Kanjana (Journal of Social Science and Cultural, 2024)
This research aims to study the environment, problems, and competency factors related to the innovation competency model of dance teachers for learning management by using qualitative research. The sample group was purposively selected, consisting of 20 executives at the institute and the College of Dramatic Arts. In-depth interviews were used as the research tool. Content data were analyzed. The research results found that the Bunditpatanasilpa Institute, Ministry of Culture, is an institution specialized in arts and culture. It offers a Bachelor of Education in Performing Arts Education and a Bachelor of Arts in Thai Dance. The teaching and learning of dance has specific characteristics and affects the concept of the characteristics of individuals who will enter the Bunditpatanasilpa Institute and the College of Dramatic Arts. Dance teachers still lack technological and language skills. However, due to the nature of the profession, it is necessary to have competency in various areas, including personal competency, learning management competency, learning and innovation competency, knowledge and self-development competency, and competency that needs to be increased, including innovation and creativity competency, measurement and evaluation of efficiency in creating innovation in learning management. and competence in information, media and technology. The research has the following recommendations: 1) Silpa Institute should create a project to develop human resources in technology and support the use of technology in teaching for teachers and students. 2) Silpa Institute should create a project to develop human resources competence in language in teaching for teachers and students. 3) Silpa Institute should set up a mentor teacher system to share knowledge between newly graduated teachers and teachers with long experience in technology and various knowledge related to teaching performing arts.